Power and Poetics: A Literary and Cultural Study of Al-Mutannabi’s Self-Glorifying Odes in The Abbasid Era - Laela, Laela Tusa’adah; Sakinah, R. Myrna Nur Sakinah (Kitabina: Jurnal Bahasa dan Sastra Arab, 2025)
This study analyzes ten selected poems by Al-Mutanabbi, a prominent poet of the Abbasid period, through literary and cultural lenses. Known for his grandiose self-representation, Al-Mutanabbi utilized the Arabic qasida form not merely for praise, but as a medium to construct a heroic poetic persona. This paper aims to investigate how Al-Mutanabbi’s verse functions as a discursive space where power, identity, and poetics converge. Using a formalist literary approach (Wellek & Warren) and supported by cultural poetics (Greenblatt) and Islamic literary theory (Stetkevych), the study explores Al-Mutanabbi’s rhetorical devices—such as metaphor, hyperbole, and parallelism—and the ideological messages embedded in his language. The research finds that Al-Mutanabbi’s poetry is not only a reflection of Abbasid court culture, but also a tool of cultural self-fashioning, where the poet elevates himself above patrons and rulers. Ultimately, the study reveals that Al-Mutanabbi transformed classical Arabic poetry into a platform of intellectual resistance and symbolic power, redefining the role of the poet within Islamic cultural history. His work serves as both a literary monument and a declaration of sovereignty over meaning, highlighting the capacity of language to shape identity and authority in early Islamic civilization.